Multimedia Interface In Smart Home Monitoring - Mansor, Yaakob (2002)
Smart home environment monitoring systems will incorporate more and more multimedia information and technology, bringing a sense of visual reality into the control room and providing more effective communication using a richer vocabulary of media This is a prototype system where the top 80%, approximately, of the window is associated with the console-based interface and the bottom 20% with the command based interface This Multimedia Interface (MUI) prototype is to convey as much possible information in the main screen display as possible, without forcing the user to burrow down through different layers of screens or menus Secondly to facilitate user-initiated changes to the system with minimal mouse/keyboard action (console) or keyboard (command-based) action on the user's part Lastly to facilitate rapid learning on the user's part, and to couple the visual feedback of both systems so that command-based system changes are indicated on the console-based system and vice-versa The console-based interface is activated by clicking on the appropriate widget like buttons in most cases, check boxes and radio buttons for a few systems The prototype command-based interface includes an edit box at the extreme bottom of the screen, where the user can type a command The user then clicks on the "Process Command Line" button to execute the command Immediately above the edit box is a list box (read only) in which the user's command is duplicated, and then followed by the program's response The results are based on analytical results, questionnaire analysis and console and command based interface results From the results tell that the prototype interface is very easy to use, and that no real major changes need to be made in order to increase learn ability The analysis also showed that the open standards and security is a priority of designing the multimedia interface of smart house.